Perceptions of Family Physician Trainees and Trainers Regarding the Usefulness of a Virtual Community of Practice - Barnett, Stephen; Jones, Sandra C; Bennett, Sue; Iverson, Don; Bonney, Andrew (JMIR Publications, 2013)
BackgroundTraining for Australian general practice, or family medicine, can be isolating, with registrars (residents or trainees) moving between rural and urban environments, and between hospital and community clinic posts. Virtual communities of practice (VCoPs), groups of people sharing knowledge about their domain of practice online and face-to-face, may have a role in overcoming the isolation associated with general practice training. ObjectiveThis study explored whether Australian general practice registrars and their supervisors (trainers) would be able to use, and would be interested in using, a VCoP in the form of a private online network for work and training purposes. It also sought to understand the facilitators and barriers to intention to use such a community, and considers whether any of these factors may be modifiable. MethodsA survey was developed assessing computer, Internet, and social media access and usage, confidence, perceived usefulness, and barriers, facilitators, and intentions to use a private online network for training purposes. The survey was sent by email link to all 139 registrars and 224 supervisors in one of Australia's 17 general practice training regions. Complete and usable responses were received from 131 participants (response rate=0.4). ResultsMost respondents had access to broadband at home (125/131, 95.4%) and at work (130/131, 99.2%). Registrars were more likely to spend more than 2 hours on the Internet (P=.03), and to use social media sites for nonwork purposes (P=.01). On a 5-point Likert scale, confidence was high (mean 3.93, SD 0.63) and was negatively associated with higher age (P=.04), but not associated with training stage. Social media confidence was lower, with registrars more confident than supervisors for almost all social media activities. On a 5-point Likert scale, overall usefulness was scored positively (n=123, mean 3.63, SD 0.74), and was not significantly associated with age or training level. The main concerns of respondents were worries about privacy (registrar: 61/81, 75.3%; supervisor: 30/50, 60.0%) and insufficient time (registrar: 41/81, 50.6%; supervisor: 36/50, 72.0%). Using a multivariate generalized linear regression model, training stage and perceived usefulness were positively predictive, and concerns about privacy and time were negatively predictive of intention to use a private online network. ConclusionsGeneral practice registrars and supervisors are interested in using a private online network, or VCoP, for work and training purposes. Important considerations are the extent to which concerns such as privacy and usefulness may be overcome by training and support to offset some other concerns, such as time barriers. Participants at an early stage in their training are more receptive to using an online network. More senior registrars and supervisors may benefit from more training and promotion of the online network to improve their receptiveness.